Micropropagation, agro-environmental studies and pharmacological activities of saffron (Crocus sativus L.) grown in controlled environmental conditions / Asif Khan - Asif , Khan (2024)
Saffron is derived from three stigmatic lobes of Crocus sativus flowers, an autumn-flowering herb that is propagated solely through clonal corm multiplication. Despite its growing market demand and potential value, the saffron yield is low due to its sterile nature and distinctive eco-physiological characteristics. This study aims to explore in vitro cormlet formation, the effect of agro-environmental factors and gamma irradiation on saffron growth indices in Malaysia and its potential nutraceutical importance of different parts of the saffron plant. It was observed that treatment of corms with 70% ethanol followed by washing in 40% clorox and 0.2% HgCl2 ensured clean aseptic viable cultures. MS enriched with BAP (4 mg/l) and IAA (1 mg/l) resulted in maximum buds sprouting response and multiple shoot primordia. Further sub culturing of shoot primordia in BAP (6 mg/l) and IAA (0.5 mg/l) was superior for achieving multiple shoots proliferation. MS supplemented with GA3 (4 mg/l) and 4% sucrose guaranteed highest cormlet number and cormlet weight, whereas GA3 (2 mg/l) and 2% sucrose gave highest root number and root length. In an attempt to assess the response of saffron growth and yield components to temperature, mother corm size, type of fertilizer and planting depth during the first two years, it was shown that lower temperature of 18 °C, bigger sized of planted corms and cattle manure application were the most favorable conditions for the entire reproductive and vegetative attributes of saffron irrespective of planting depth. Likewise, different doses of γ-rays (0, 10, 20, 30, and 40 Gy) was evaluated for their potential effect on morpho-agronomic characteristics of saffron and the results indicated that 10 Gy treatment stimulatively effected on various vegetative attributes, whereas radiation at 20 Gy was the most optimal dose for the reproductive traits of saffron. Also, one of the 20 Gy plants showed four irregular dark petals, tetrafid stigma, and two stamens compared with six normal-sized petals, trifid stigma, and three stamens in control. Conversely, higher doses of 30 Gy and 40 Gy were lethal by showing deleterious effects in terms of saffron growth indices. Saffron parts i.e corm, leaf, petal and stigma obtained were further evaluated for their toxicity and pharmacological activities in mice. During the 14 days oral toxicity study, none of the saffron ethanolic extracts at a dose of 2000 mg/kg body weight showed any mortality and abnormality in all selected parameters in mice of both sexes as compared with their respective control groups. Stigma and petal ethanolic extracts showed significant enhancement behavior in carrageenan induced hind paw edema assay and hot plate analgesic assay as well as antidepressant test and anticoagulant test in mice. However, leaf and corm ethanolic extracts displayed mild activity. Likewise, SEE followed by PEE exhibited antihyperglycemic effect and showed strong hypolipidemic response in STZ-induced diabetic mice. The SEE and PEE treatment to diabetic mice also significantly restored the level of serum glucose, kidney and liver biomarkers towards the normal control which validate its use as an antidiabetic drug in folk medicine.